Insider e outsider nel mercato del lavoro italiano - Marra, Claudio; Turcio, Sandro (Argomenti, 2016)
“Inequalities start in the labour market” has recently warned the ILO in the Global Wage Report 2014/2015. The most recent interpretations look at polarization as a growing social issue. On this track, we took up and dropped over the Italian labour market tools, concepts and methods (such as the insider outsider theory, vulnerable employment, decent work, labor market attachment) in order to rebuild, through the Istat’s labour force survey, the occupational structure of the country up to the crisis’s possible turning point. The hypothesis that emerges is the polarization of employment in which outsiderness might become a determinant factor in the prolonged stagnation of inequalities.